Diseño del sistema de abastecimiento de agua y drenajes para la parroquia Zambi, del cantón Catamayo, provincia de Loja - Morocho Guaillas, Junior Alex (2018)
Abstract:The aim of this study is to carry out the "Design of the water supply and drainage system for the parish Zambi, of the canton of Catamayo, province of Loja", project developed through agreement between the Private Technical University of Loja (UTPL), Foundation for the Business and Social Development (FEDES) and Decentralized Autonomous Government of the canton of Catamayo, with which through its execution will allow the improvement of the quality of inhabitants life of the study area and reduce the shortage of vital liquid, the rate of water-borne diseases, unhealthy and environmental pollution. It is determined the baseline through: socioeconomic surveys, demographic study, topographic survey, water quality analysis, soil testing, hydrological study and evaluation of existing water and sanitation systems. It is effected the design of the potable water system, sanitary and storm sewer system based on technical criteria and guidelines established by the Ecuadorian regulations for the design of water supply systems, disposal of excreta and liquid waste.